2012
DOI: 10.1002/ejlt.201200003
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile, oxidative stability, and sensory properties of breast meat from turkeys fed diets with a different n‐6/n‐3 PUFA ratio

Abstract: The objective of this study was to determine the effect of diets with a different n-6/n-3 PUFAs ratio (7.31, 4.43, and 0.99), resulting from the addition of different dietary oils: soybean, rapeseed, and linseed (diets S, R, and L, respectively), on the fatty acid (FA) profile, oxidative status, and sensory properties of turkey breast meat. After 15 wk of feeding, breast meat yield and chemical properties of the meat were similar in all groups. Raw breast meat of R turkeys had a significantly higher content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
4
25
1
Order By: Relevance
“…This supports the findings of many studies that the fatty acid profile of chicken meat depends on the dietary polyunsaturation level (Nguyen et al, 2003;Cortinas et al, 2004;Bou et al, 2005;Koreleski and Świątkiewicz, 2006;Jankowski et al, 2012). Increased dietary levels of vitamin E or both antioxidants in the diets with rape seeds and fish oil was associated with a lower n-6 PUFA content in breast and thigh meat and lower content of n-3 PUFA in thigh meat in comparison with group RF.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This supports the findings of many studies that the fatty acid profile of chicken meat depends on the dietary polyunsaturation level (Nguyen et al, 2003;Cortinas et al, 2004;Bou et al, 2005;Koreleski and Świątkiewicz, 2006;Jankowski et al, 2012). Increased dietary levels of vitamin E or both antioxidants in the diets with rape seeds and fish oil was associated with a lower n-6 PUFA content in breast and thigh meat and lower content of n-3 PUFA in thigh meat in comparison with group RF.…”
Section: Discussionsupporting
confidence: 89%
“…It is responsible for unpleasant odours, loss of texture, consistency, appearance, and nutritional value of the meat (Perez et al, 2010;Jankowski et al, 2012). The thiobarbituric acid reactive substances (TBARS) test is a method often used for the detection of lipid oxidation in food.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive effect of rapeseed oil (RO) on increasing of PUFA and n-3 FA in chicken meat was documented (Haugh et al 2011). Similarly, Jankowski et al (2012) observed higher concentration of linolenic acid, PUFA, and improved n-6/n-3 ratio in turkeys fed RO in comparison with soybean oil.…”
mentioning
confidence: 96%